La Alcestis de Eurípides: una nueva hipótesis sobre su mito - Bolaños López, Zahyra (2013)
Most of the human`s psychological processes belong to the realm of the unconscious, within which all vital activity originates, makig possible to explain many of the unexpected reactions of human behavior. The unconcious is not a deadly abysm, but it contains all those creative and nutritional forces of being. For Jung -it does not mean a going backwards- rather, the Euripides´Alcestis presents a necessary process which must be valued in a positive way.